2023
DOI: 10.1177/19485506231153017
|View full text |Cite
|
Sign up to set email alerts
|

The Between-Person and Within-Person Effects of Intergroup Contact on Outgroup Attitudes: A Multi-Context Examination

Abstract: The extensive literature on the contact hypothesis reports a positive association between intergroup contact and outgroup attitudes, yet it remains unknown whether this association reflects within-person (i.e., situational changes within individuals) or between-person (i.e., stable differences between individuals) effects. To investigate this question, we applied (random-intercept) cross-lagged panel models in two studies featuring different samples, measurements, and contexts. We found longitudinal contact–at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
3
11
0
Order By: Relevance
“…It is also interesting to notice that while we found strong evidence of within‐person simultaneous associations between intergroup contact and intergroup outcomes, existing evidence supporting within‐person lagged associations (considering various outcomes related to perception, attitudes and emotions), mostly derived from RI‐CLPMs, is weaker (Barlow et al., 2019; Bohrer et al., 2019; Friehs et al., 2023; Sengupta et al., 2023). These findings of prior studies are not in contrast with the results of the present study: it is likely that fluctuations of intergroup contact are more associated with fluctuations of attitudes and emotions in the present (i.e., the same moment or the same time period) than with fluctuations of attitudes and emotions in a subsequent moment.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…It is also interesting to notice that while we found strong evidence of within‐person simultaneous associations between intergroup contact and intergroup outcomes, existing evidence supporting within‐person lagged associations (considering various outcomes related to perception, attitudes and emotions), mostly derived from RI‐CLPMs, is weaker (Barlow et al., 2019; Bohrer et al., 2019; Friehs et al., 2023; Sengupta et al., 2023). These findings of prior studies are not in contrast with the results of the present study: it is likely that fluctuations of intergroup contact are more associated with fluctuations of attitudes and emotions in the present (i.e., the same moment or the same time period) than with fluctuations of attitudes and emotions in a subsequent moment.…”
Section: Discussionmentioning
confidence: 58%
“…Previous research showed that while there is some evidence for within‐person simultaneous associations between intergroup contact and prejudice, evidence for within‐person lagged associations is weak, especially when employing RI‐CLPMs (e.g., Bohrer et al., 2019; Friehs et al., 2023; Sengupta et al., 2023). Although more evidence is needed to confirm this pattern, one explanation for it is that the effect of contact on intergroup outcomes could mainly unfold in the short term, rather than in the long term.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3We note that the observed pattern of between-person effects in the absence of within-person effects has been found in research that examines specific group contact (e.g., Friehs et al, 2023; Sengupta et al, 2023), but also using our approach of asking British participants about contact with less specified others (“foreigners”). Regardless, future research would be advised to further explore the implications of precision and specificity regarding not only the intervals but the contact group itself.…”
mentioning
confidence: 88%
“…Although there are alternative methods for separating between-person and within-person effects, RI-CLPMs are the most likely to converge (Orth et al, 2021) and do not require intensive longitudinal data (e.g., over 30 assessments). Thus, RI-CLPMs are quickly becoming the method of choice amongst longitudinal researchers interested in within-person effects (Friehs et al, 2023; O’Donnell et al, 2021; Osborne & Little, in press). Here, we apply this model to test, for the first time, whether levels of ingroup and outgroup contact predict within-person change in perceived discrimination over time.…”
Section: Studymentioning
confidence: 99%